Atención al público del gobierno autónomo descentralizado de la Parroquia Pimocha - Ilvay Caranqui, Jorge Luis (2019)
The legal regulations that govern Ecuador, have allowed the decentralization of power, so the administrative management of the parishes is not done directly from the Mayor's Office, there are now the Gads Decentralized Autonomous Governments, who are responsible for determining the needs of the community and propose that they be satisfied by the cantonal government. The human element is the axis of the success or failure of an organization, be it public or private; The relationship of staff directly with the public is of the utmost importance, because on this relationship depends the success or failure of the management of managers. The attention to the public depends on the training of the personnel in charge of this task within the organization, for which it is necessary that you have a professional training in human relations, so that you know how to attend to the different types of people, especially in the institutions public, where an economic utility is not sought, but a service that is generally free in favor of citizens. The study developed has allowed us to determine the customer service offered in a public institution, that is, the Gad of the Pimocha Parish, of the Babahoyo canton, province of Los Ríos, considering the mission and vision of the organization. It is important to indicate that when talking about public service or customer service, we are directly related to the quality of public services, which must evolve towards a constant improvement that allows meeting the community's requirements, in this case of the inhabitants of the parish Pimocha